Work Ethic of Muslim Traders in Palakka Central Market, Bone Regency and its Effect on Increasing Economic Welfare - Jumriani Jumriani,; Syahidah Rahmah; A. Cahaya; M. Awaluddin; Feby Triadi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
A high work ethic is needed in completing a job. The problem is studied in this study to see the work ethic of Muslim traders in running their business and its effect on improving their welfare. There are approximately 450 traders in the Central Market. The research method used in this research is to use a quantitative approach. The data collection techniques used in this study were using a questionnaire, interview, and documentation. The data analysis used is descriptive statistical analysis and inferential statistical analysis. The ability of the independent variable to explain the variance of the dependent variable is 56 percent. This means that there is 44 percent (100 percent - 56 percent) of the variance of the dependent variable which is explained by other factors. This means that the work ethic variable has an effect of 56.0% on the improvement of the economic welfare of Muslim traders in Palakka Market, Bone District